EP1040 Engineered bovine-milk-exosome-mediated delivery of resibufogenin and its enhanced suppression effect in platinum-resistant ovarian cancer cells. (1st November 2019) - Zhou, G; Ding, J
Abstract : Introduction/Background: Platinum-resistant ovarian carcinoma presents poor prognosis owing to its chemotherapeutic resistance. Numerous studies reported that exosomes are naturally occurring membrane particles that mediate intercellular communication by delivering molecular information between cells. Herein, we investigated whether bovine-milk-derived exosomes as carriers of resibufogenin (RBG) could inhibit platinum-resistant ovarian carcinoma and what is the specific mechanism. Methodology: First, exosomes and exosome-encapsulated resibufogenin were isolated using differential centrifugation and were characterized by electron microscopy, nanoparticle tracking analysis, and western blot. Then, the loading efficiency was measured by Ultra Performance Liquid Chromatography-tandem mass spectrometry (UPLC-MS) method. Then, the anti-cancer efficacy of exosome-mediated drug was assessed in vitro and in vivo. Meanwhile, the distribution of Milk-exosome-RBG in cells was inspected by confocal microscopy. High-throughput RNA sequencing was used to detect and verify the targeted pathways and GO analysis and western blot were applied to clarify the function. Results: Bovine-milk-derived exosomes, which expressed CD63 and TSG101 and ranged from 35 to 201 nm, loaded resibufogenin with certain loading efficacy(A and B). Bovine-milk-derived exosomes delivered resibufogenin into platinum-resistant ovarian carcinoma(E, F), the dose-depended process enhanced the cytotoxicity of resibufogenin(C). In vivo experiment demonstrated that intragastric administration of milk-exosome-RBG suppressed the growth of xenograft tumors(D), the effect of which was superior to that of intraperitoneal injection of resibufogenin, and had lower ki-67 expression and higher tunel expression. The mRNA sequencing assay(G), qPCR assay, immunohistochemistry assay and western blotting assay showed that the PI3K/AKT and Regulation of actin cytoskeleton signaling pathways accounted for the results above. Conclusion: Bovine-milk-exosome may be used as effective carriers in delivering resibufogenin into platinum-resistant ovarian carcinoma via clathrin-independent endocytosis and macropinocytosis. Bovine-milk-exosome-RBG enhancing resibufogenin's cytotoxicity in vitro and in vivo through PI3K/AKT and Regulation of actin cytoskeleton signaling pathway. This study supports the potential use of bovine-milk-exosome as a drug carrier for the treatment of platinum-resistant ovarian carcinoma. Disclosure: Nothing to disclose